Genome-Wide Identification and Expression Analyses of the MADS-Box Gene During Flowering in Primulina huaijiensis - Jie Zhang; Xinxia Cai; Qin Liu; Ziyi Lei; Chen Feng (Plants)
Primulina huaijiensis is a promising candidate for eco-bottle flowers, yet the genes related to flowering remain unexplored despite the availability of genomic data for several years. MADS-box genes constitute a large family of transcription factors that play crucial roles in plant growth and development, particularly in flower development. In this study, we identified 84 MADS-box genes (PhuMADS) in P. huaijiensis genome and analyzed their evolution and expression profiles to gain insights into the flowering mechanism. The 84 genes constitute 29 type I and 55 type II MADS-box genes. Phylogenetic analysis further classified them into 17 subfamilies, which were randomly distributed across 18 chromosomes and four scaffolds. PhuMADS genes exhibit a range of 1 to 12 exons and share conserved motifs. Segmental duplication was found to be the primary driver of PhuMADS gene family expansion, with duplicated gene pairs undergoing purifying selection. Cis-acting elements analysis revealed PhuMADS promoters harbor abiotic stress-, hormone-, light-, and growth-related motifs, implicating roles in development and environmental adaptation in P. huaijiensis. RNA-seq showed distinct expression patterns of PhuMADS genes among different tissues or developmental stages. The results of qRT-PCR analysis of selected genes further validated the RNA-seq findings, suggesting these genes may exert distinct functional roles during floral development. This study laid a theoretical foundation for further functional studies of the MADS-box genes in P. huaijiensis.